letters. (New Statesman, 2003)
Presents letters to the editor of "New Statesman". Criticism of the October 20 evaluation of the Thatcher/Major governments by Douglas Hurd; Comment on the Richard Reeves article concerning early childhood development and education; Implication of a statistical error in the October 13 article by Patrick Hosking; Other topics including female fans in football.